THE INFLUENCE OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTION APPAREL PRODUCTS - Adinda Surgana; Heriyana; Muchsin; Sapna Biby (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to analyze the influence of social media marketing on intention to purchase clothing products. Social media marketing is seen from several dimensions, namely interactivity, informativeness, personalization, trendiness and WOM. Data for this research was collected through a survey method using a questionnaire as a data collection instrument. The respondents in this research were 108 respondents. This research uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The research results show that partially Interactivity has a significant effect on the intention to buy Rabbani products, Informativeness has a significant effect on the intention to buy Rabbani products, Personalization has a significant effect on the intention to buy Rabbani products, Trendines has a significant effect on the intention to buy Rabbani products and Worth of mouth has a significant effect on the intention to buy Rabbani products. Simultaneously, interactivity, informativeness, personalization, trendiness and worth of mouth have a significant effect on the intention to purchase Rabbani products.